An Investigation of Secondary School Students' Participation Levels in Recreational Activities and Their Attitudes Towards Physical Education Classes: The Case of Sultangazi (Journal of Management and Educational Sciences, 2025)
The purpose of this study is to examine the relationship between secondary school students' levels of participation in recreational activities and their attitudes towards physical education classes. The survey model, one of the quantitative research methods, was used. The sample of the study consisted of 610 high school students (383 female, 227 male) studying in the Sultangazi district of Istanbul. Data were collected using the ‘Short Form of the Leisure Attitude Scale (SZTÖ-KF)’ and the ‘Physical Education Class Attitude Scale’. Descriptive statistics, t-tests, ANOVA, and multiple regression analyses were used to analyse the data. Findings indicate that students' attitudes towards free time and physical education classes are generally high. Significant differences were found based on gender and age variables; male students scored higher on all sub-dimensions, and attitude levels decreased with age. Furthermore, it was observed that the cognitive, affective, and behavioural dimensions of leisure time attitudes significantly predicted attitudes towards physical education classes. Consequently, it can be stated that participation in recreational activities strengthens students' positive attitudes towards physical education classes and plays an important role in fostering lasting habits towards physical activity.